Synthesis of Acidic Heterogeneous Catalysts with High Stability Based on Graphene Oxide/Activated Carbon Composites for the Esterification of Lactic Acid - Thu Ha Thi Vu; Manh Ha Nguyen; Minh Dang Nguyen (Journal of Chemistry)
In this article, acidic heterogeneous catalysts based on graphene oxide and sulfonated biochar were prepared, characterized, and used for lactic acid esterification to form ethyl lactate. Graphene oxide was supported on activated carbon (GO/AC) to more easily filter the catalyst from the reactants. The catalysts were characterized by such methods as XRD, FT-IR, SEM, BET, and the acid-base titration. Catalytic activity was evaluated through the esterification of lactic acid. As a result, the activity of the catalysts decreased in the following order: graphene oxide > sulfonated biochar ≈ GO/AC >> activated carbon. In addition, the GO/AC catalyst showed good stability with an unchanged yield from the 3rd to the 6th recycling test. These results suggest potential applications for new acidic heterogeneous catalysts based on graphene oxide and sulfonated biochar that could replace homogeneous acids in the future.